Correlation Of Malnutrition Status With Malaria Incidents In Children Under 5 Years Old - Pratama A., Ronald; Bimantara, Riza Fajar; Arundani, Prima; Biutifasari, Verna; Mertha Adnyana, I Made Dwi (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2024)
Malaria is a prevalent disease that continues to affect infants and results in the death of over 435,000 individuals worldwide, with children under the age of five accounting for 11-30% of these fatalities. Malnutrition afflicts millions of children worldwide, especially in Indonesia, and is the leading cause of mortality among toddlers. Investigate the correlation between malnutrition and the occurrence of malaria in children under the age of five. Additionally, explore the prevalence, factors that contribute to the risk, and underlying processes of both malaria and malnutrition. This study utilized 15 internationally recognized scholarly articles to investigate the correlation between malnutrition and the prevalence of malaria in children below the age of five. According to the analysis of 10 scholarly studies, the occurrence of malaria and malnutrition among children under the age of five remains significantly elevated, particularly in African nations, various countries in South Asia, Southeast Asia, the Middle East, Central America, and South America. The analysis of 3 journal papers examined the risk factors associated with malaria and malnutrition, specifically focusing on age, environment, sanitation, economy, education, food availability, and residing in refugee camps. After reviewing 9 journal publications, it has been shown that malnutrition is a risk factor for malaria. Additionally, one of the articles suggests that children who are malnourished have a reduced likelihood of contracting malaria. The findings of this scoping review indicate a bidirectional correlation between malnutrition and the occurrence of malaria in young children.